Green Synthesis of Mixed Metal Oxide (MnO, CuO, ZnO) Nanoparticles (NPs) using Rose Petal Extract: An investigation of their Antimicrobial and Antifungal Activities - Syeda Shaista Gillani; Sana Abbas Khan; Rabia Nazir; Aisha Waheed Qurashi (Scientific Inquiry and Review, 2021)
In this study, mixed metal oxide (CuO, ZnO, and MnO) nanoparticles (NPs) were synthesized via the green process, which is considered to be simple, cost-effective, eco-friendly, and non-toxic. During the green synthesis method, rose petal extract was used as a reducing and capping agent, while salt solutions (CuCl2, MnCl2, and ZnSO4) were used for the bio-reduction of metal precursors, leading to the formation of mixed metal oxide (CuO, ZnO, MnO) NPs. UV-Visible and FTIR spectroscopy were used for the analysis of mixed metal oxide (CuO, ZnO, MnO) NPs. The results showed maximum absorbance of the mixed metal oxide in the range of 280 to 370 nm. The presence of particular peaks in FTIR verified the synthesis of mixed metal oxide nanoparticles. Subsequently, the antimicrobial and antifungal activities of mixed metal oxide (CuO, ZnO, MnO) NPs were tested by using the disc diffusion method and well diffusion method. Mixed metal oxide (CuO, ZnO, MnO) NPs displayed antimicrobial activity against Escherichia coli and antifungal activity against Candida albicans, Curvularia lunata, Aspergillus niger, and Trichophyton simii. Hence, these mixed metal oxide (CuO, ZnO, MnO) NPs can be effectively used in the pharmaceutical sector.Keywords: antifungal, antimicrobial, green synthesis, mixed metal oxides nanoparticles (MONPs), rose petals extractsCopyright (c) The Authors